2013
DOI: 10.2111/rem-d-12-00136.1
|View full text |Cite
|
Sign up to set email alerts
|

Site, Competition, and Plant Stock Influence Transplant Success of Wyoming Big Sagebrush

Abstract: Within the sagebrush steppe ecosystem, sagebrush plants influence a number of ecosystem properties, including nutrient distribution, plant species diversity, soil moisture, and temperature, and provide habitat for a wide variety of wildlife species. Recent increases in frequency and size of wildfires and associated annual grass expansion within the Wyoming big sagebrush alliance have increased the need for effective sagebrush restoration tools and protocols. Our objectives were to quantify the success of Wyomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…Although establishment of mature A. tridentata stands can take several decades (Miller et al . ), little increase in cover or density of this species 8–21 years after seeding suggests alternative strategies, such as transplanting, may be required to establish meaningful populations (McAdoo, Boyd & Sheley ). While our results suggest that B. prostrata seeding can increase shrub cover, concerns have emerged regarding its potential spread to unseeded areas (Gray & Muir ).…”
Section: Discussionmentioning
confidence: 99%
“…Although establishment of mature A. tridentata stands can take several decades (Miller et al . ), little increase in cover or density of this species 8–21 years after seeding suggests alternative strategies, such as transplanting, may be required to establish meaningful populations (McAdoo, Boyd & Sheley ). While our results suggest that B. prostrata seeding can increase shrub cover, concerns have emerged regarding its potential spread to unseeded areas (Gray & Muir ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, on average, the habitat quality of the latter three plot types is approximately equally limited by plot (i.e., native species regeneration or treatment success) and landscape conditions, whereas habitat quality in mixed-treatment and unburned areas is more limited by landscape composition. Treatment technique limitations are currently being addressed through using seeds with local genotypes, low-or no-till rangeland drills, novel approaches for seed application (e.g., using imprinters for seeds that should not be buried, coating seeds prior to sowing) (Monsen et al 2004, Shaw et al 2005, Madsen et al 2012a, Madsen et al 2012b, and planting seedlings (Dettweiler-Robinson et al 2013, McAdoo et al 2013. Landscape limitations on sage-grouse occupancy were not unexpected since ESR sites are, by definition, in need of restoration action and they are often imbedded in disturbanceprone locations.…”
Section: Predicted Probability Of Sage-grouse Occupancy In Restoratiomentioning
confidence: 99%
“…Thus, it is important to know whether ESR treatments provide an ancillary benefit to sage-grouse. Further, these projects represent an important sage-grouse conservation opportunity for three reasons: (1) ESR projects constitute by far the largest number of hectares treated and dollars spent on restoration in the Great Basin (e.g., $60 million in 2007), (2) most individual ESR projects (73%) cite a need to improve wildlife or sage-grouse habitat as specific project objectives or concerns (these projects account for 1.6 million ha, or 81% of all hectares treated since 1990 according to LTDL data), and (3) studies have found that native plant restoration in degraded areas is significantly more successful when preceded by non-native plant removal via fire or other means (Davies 2010, McAdoo et al 2013, Miller et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the studies investigating sagebrush recovery from plantings have been conducted at relatively small scales (Davies et al ; Dettweiler‐Robinson et al ; McAdoo et al ). Therefore, there is a need to evaluate variability in outplant success over larger and more variable areas representative of actual restoration sites, with consideration that sagebrush subtaxa may exhibit different survival patterns across the landscape.…”
Section: Introductionmentioning
confidence: 99%